The heterogeneous impacts of import competition on Mexican manufacturing plants - Juan S. Blyde; Oscar Fentanes (Inter-American Development Bank (IDB), 2019)
We study the impact of import competition on Mexican firm outcomes between 2003 and 2013 by exploiting variation in import penetration across industries. Focusing on the increase in import competition from China that Mexico experienced during this period, we find that the trade shock induced a decline in employment, sales, exports, and productivity. Importantly, the results show that the average impact hides significant heterogeneity effects, with smaller and less efficient plants experiencing the largest adjustments, while the most efficient plants exhibited relatively minor effects and, for some outcomes, no effects at all. The existence of heterogeneous impacts across establishments is consistent with other sets of findingsfor instance, that the productivity gap between small and large plants has been increasing over time and that the reallocation of resources has been productivity-enhancing, particularly in sectors that have experienced large-scale import penetration from China.
Keywords: F14; F61; L25; L60; 330; import competition; manufacturing plants; productivity